Teacher is a condition factor in education of the Ukrainian philosophical world view - Pazynich S.N (Kharkov National Pedagogical University, 2010)
Questions are examined about the necessity of development of Ukrainian philosophy - theoretical foundation of world view and at the same time as bases integral to socially-spatial systems of the Free State. A thesis is grounded about an attributive function in development of national philosophy of concept - «Why edges». A problem is formulated about state approach in relation to development of philosophical culture in a country and bringing in this important business all and singular teachers and student young people.